APLIKASI TEKNOLOGI BERBASIS ANDROID SEBAGAI UPAYA PEMBERDAYAAN CAREGIVER LANSIA DI SURABAYA - Efendi, Ferry; Indarwati, Retno; Nihayati, Hanik Endang; Susanti, Ika Adelia; Asih, Meirina Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The elderly experience a decreased ability to carry out independent activities, and the role of the family as a caregiver is needed in helping their care. Caregivers need to obtain information related to knowledge and skills in caring for the elderly, but there is lack of effective media that can be used at this time. Particularly online media which are convenience, flexible and can be used any time by all caregiver at their house. This community service aimed to help overcome the problems of partners, especially the Panca Hebat Elderly Communities in Surabaya. It helps caregivers to meet the care needs of the elderly in the community. The method used developing an android caregiver application for the elderly and training to increase caregivers in caring for the elderly. The elderly caregiver application has been used by 123 users consisting of caregivers and the elderly. The results of the evaluation of socialization and training also found differences in knowledge between participants before and after community service (p-value 0.000). The results of this evaluation indicate that community service related to the use of caregiver applications can increase the knowledge of elderly caregivers.